2019
DOI: 10.29252/dsme.6.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment of faculty members' educational needs in order to empower them at Shahrekord University of Medical Sciences

Abstract: Introduction: Faculty members are considered as basic resources of every university. Therefore, educational needs assessment in order to empower most faculty members is an inseparable part of educational planning. Methods: The study was conducted using a descriptive cross sectional method. The population consisted of university professors. About 65% professors participated. The reliability and validity of data collection tool, a self-made researcher questionnaire, was approved according to different studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 2 publications
4
17
1
Order By: Relevance
“…6,32 Algahtani et al found that a majority of faculty members considered research-related aspects to be a less important program, 4 which is consistent with Karimi's study, where less than 50% of participants expressed interest in research. 6 Consistent results have been documented by other researchers as well. 5,32 Our study found lower priority levels for the research domain 3,9 and the use of digital libraries (search in scientific literature and databases), 8,11 in contrast to previous research.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…6,32 Algahtani et al found that a majority of faculty members considered research-related aspects to be a less important program, 4 which is consistent with Karimi's study, where less than 50% of participants expressed interest in research. 6 Consistent results have been documented by other researchers as well. 5,32 Our study found lower priority levels for the research domain 3,9 and the use of digital libraries (search in scientific literature and databases), 8,11 in contrast to previous research.…”
Section: Discussionmentioning
confidence: 52%
“…In the literature, other studies have reached similar conclusions about faculty need for personal development 16,19–21 . Nonetheless, curriculum design received less than half the vote in the Karimi research, 6 and teachers reported feeling most effective in personal development in the Yenen study's 3 …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations